Implementasi Sistem Informasi Arsip Berbasis Web pada Bapperida Kabupaten Kudus - Selamet Ahmad Faisal; Eko Darmanto (CV. ITTC INDONESIA, 2026)
Manual archive management at Bapperida Kabupaten Kudus creates challenges in document retrieval, storage, and monitoring processes, resulting in less optimal administrative services. This community service activity aimed to improve employees’ understanding and skills in utilizing a Web-Based Archive Information System to support more effective and efficient archive management. The implementation method included needs analysis, system design, training implementation, evaluation, and follow-up monitoring. The training was conducted for three days involving five employees of Bapperida Kabupaten Kudus. Evaluation techniques were carried out through pre-tests, post-tests, practical observations, and Likert-scale questionnaires to measure participants’ understanding and acceptance of the system. The results showed an increase in participants’ understanding, indicated by the improvement of the average pre-test score from 60 to 85.8 in the post-test. In addition, questionnaire evaluation results showed positive responses with an average score of 4.34 on aspects of system usability, archive retrieval speed, document management accuracy, and system benefits for work activities. The implementation of this system proved effective in improving archive management efficiency and supporting administrative digital transformation within Bapperida Kabupaten Kudus.